Effects of honeycomb polysaccharides on growth performance, slaughter performance, antioxidant capacity, and immune function in Cyan-Shank Partridge chickens - Zhang, Haibo; Yin, Ling; Zhang, Jingqi; Yan, Guiqin (Frontiers in Animal Science, 2025)
There has been increased awareness of the negative effects of antibiotic use in poultry production, necessitating research on sustainable alternatives. Honeycomb polysaccharides (HPs) have attracted considerable attention due to their bioactivity. Therefore, we investigated the effects of HPs on growth and slaughter performance, antioxidant capacity, and immune function in Cyan-Shank Partridge chickens. Male Cyan-Shank Partridge chicks (n = 300; 1-day-old) were randomly assigned to five groups: negative control group (NC, fed a basal diet), three experimental groups (fed basal diet supplemented with 300 (HPs300), 600 (HPs600), or 1,200 mg/kg (HPs1200) of HPs), and chlortetracycline hydrochloride group (positive control group, PC). Compared to NC group, there was a significant increase (p < 0.05) in body weight at 20 days of age, average daily weight gain from day 1 to 20, and average daily feed intake from day 41 to 60 in the group HPs1200. Additionally, leg muscle ratio was significantly higher (p < 0.05) in group HPs1200 than in NC group. Compared with those in NC group, there was a significant decrease (p < 0.05) in serum malondialdehyde and a significant increase (p < 0.05) in serum superoxide dismutase activity in group HPs1200. Moreover, serum immunoglobulin A (IgA), IgM, and IgG levels were significantly higher (p < 0.05) in group HPs1200 than in group NC. Conclusively, HPs addition to feed at 1,200 mg/kg enhances growth performance, slaughter performance, serum antioxidant capacity, and immune function in Cyan-Shank Partridge chickens.